Karakteristik Layanan Pencegahan Prevalensi Stunting di Bolaang Mongondow Timur - Posumah, Johnny Hanny; Pombengi, Jericho D.; Rorong, Arie Junus (PANDITA: Interdisciplinary Journal of Public Affairs, 2025)
The stunting rate in East Bolaang Mongondow has increased quite significantly, reaching 346 cases or above 30%, second in North Sulawesi, so specific and sensitive interventions are needed from cross-sectoral Regional Work Units and problems found in the field. The phenomenon of stunting in school-age teenagers who marry too early, premarital sex for teenagers and unwanted pregnancies, then the lack of marriage guidance services for prospective brides and grooms by educating prospective brides and grooms to have an understanding and readiness to enter the world of marriage. as well as guidance services for family resilience to worship (sakinah). Additional food for toddlers is not optimal, the implementation of collaboration with the Village Government throughout Boltim in providing additional food (PMT) of animal protein given for three months is considered not optimal. The purpose of this study was to analyze the characteristics of stunting prevention services in East Bolaang Mongondow Regency. The expected results are that the prevalence of stunting in East Bolaang Mongondow Regency can reduce stunting cases.